Do i posle polunochi . Do i posle polunochi . Before and after Midnight . До и после полуночи - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. Interview with actress and singer Rada Volshaninova; informal meeting of actors and actresses (continuation). Featured in the program: Aroseva, Ol'ga Aleksandrovna (Actress) Contributors: Molchanov, Vladimir Kirillovich (Anchor) Беседа с актрисой и певицей Радой Волшаниновой; неформальная встреча актеров и актрис (продолжение). В программе участвуют: Аросева, Ольга Александровна (Актриса) Создатели: Молчанов, Владимир Кириллович (Ведущий/Ведущая)